Design of a plane-wave launcher in a parallel-plate waveguide - Muhammad Riduan Asmin (2019)
Ever since the creation of technologies such as handphones, televisions, and radios, engineers have been developing to meet the people's demand for services which requires a large amount of bandwidth. Services that was mentioned earlier refers to web searching, high definition interactive video and many more. To learn how such demand can be achieved, various type of transition structure designs was explored and tested. By exposing oneself to these transition structure designs, one can capitalize on its advantage and creates a design capable of meeting the demand of the people. With the help of a software, various transition structure can be designed and tested for its ability to provide wide bandwidth at low return loss. Hence, with all these measures taken, a new design will be created and tested. This final year project is broken down into 2 stages. The first stage focuses on analyzing the cone-shaped and stepped junction structure. The analysis includes familiarise oneself using the High-Frequency Structural Simulator Software (HFSS) to design and test for its Voltage Standing Wave Ratio (VSWR) and return loss. The second stage involved combining these designs by capitalize their advantage and improve on their flaws. This can be further achieved by varying different parameters of the structure to obtain a wide bandwidth with a low return loss.